Evidence of Optically Stimulated Luminescence in Lu3Al5O12:Ce. Issue 14 (26th April 2019) - Gallo, Salvatore; Veronese, Ivan; Vedda, Anna; Fasoli, Mauro
Abstract : Lutetium aluminum garnet, commonly known as LuAG, is a versatile material finding numerous optical applications, and whose scintillation properties have been widely investigated. In this study, experimental evidences of optically stimulated luminescence (OSL) phenomena occurring in LuAG:Ce crystals are shown. After demonstrating the possibility to optically bleach an electron trap responsible for a thermally stimulated luminescence (TSL) peak at 280 °C (heating rate 1.7 °C s −1 ) using red light, a direct measurement of the OSL decay curve and of the resulting characteristic Ce 3+ 5d‐4f emission spectrum is carried out. The assessment of the bleaching spectrum of the TSL peak at 280 °C reveals that light with wavelength in the 600–650 nm interval is the most efficient in depleting the TSL peak, making He‐Ne lasers suitable sources of optical stimulation. The finding of OSL features in LuAG:Ce paves the way to new application perspectives. In particular, the achievement of a good balance between scintillation and energy storage properties of LuAG.Ce can drive a constructive integration between X‐rays imaging approaches based on photo‐stimulable phosphors and those exploiting scintillating materials. Abstract : Evidence of the optically stimulated luminescence in Lu3 Al5 O12 :Ce (LuAG:Ce) crystals under red light illumination. An electron trap responsible for a thermally stimulated luminescence peak at 280 °C is efficiently depleted by light exposure, resulting in the characteristic Ce 3+ emission.